Integrasi pedagogik, teknologi, dan keilmuan dalam pendidikan guru masa kini - Khamila Amalia Nurwanto (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2026)
The rapid growth of digital technology requires pre-service teachers to develop balanced pedagogical, technological, and content knowledge. This study aims to explain the use of Technological Pedagogical Content Knowledge (TPACK) in teacher education and to identify its challenges and possible strategies in Faculties of Teacher Training and Education (FKIP). This study used the Integrative Literature Review (ILR) method to review and analyze findings from previous studies. The results show that pre-service teachers generally have better technology skills than their ability to combine technology with teaching methods and subject knowledge, indicating that all TPACK components still need further improvement. Therefore, strengthening the curriculum, providing training, and using technology appropriately might help prepare future teachers for teaching in the digital era.